2014
DOI: 10.12659/msm.890491
|View full text |Cite
|
Sign up to set email alerts
|

Tumor characteristics of breast cancer in predicting axillary lymph node metastasis

Abstract: BackgroundTumor characteristics was sought to be related to axillary lymph node metastasis (ALNM), the paramount prognostic factor in patients with invasive breast cancer. This study was aimed to identify the ALNM-associated tumor characteristics and to determine the predictive clinical pathway.Material/MethodsData from 1325 patients diagnosed with invasive breast cancer between January 2004 and January 2010 were retrospectively reviewed. The structure equation model (SEM) was used to build the predictive clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, the value of histological grade on axillary lymph node metastasis has been controversial. Histological grade was the third predictor for SLN metastasis in the present study, which was in concordance with previous reports [ 36 , 37 ]. However, in a recent report, tumor histological grade was related with SLN metastasis by univariate analysis either in overall sample or in luminal subgroup, but lost predictive value by multivariate logistic regression analysis [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, the value of histological grade on axillary lymph node metastasis has been controversial. Histological grade was the third predictor for SLN metastasis in the present study, which was in concordance with previous reports [ 36 , 37 ]. However, in a recent report, tumor histological grade was related with SLN metastasis by univariate analysis either in overall sample or in luminal subgroup, but lost predictive value by multivariate logistic regression analysis [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Studies have also reported LVI as a possible independent prognostic factor [12, 13]. However, due to limited sampling, preoperative assessment of LVI status of a tumor by core-biopsy is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Our model gave a very good balance between sensitivity and specificity; in fact, the AUC of the validated first model was almost 0.9, which implies that our model can correctly classify around 90% of patients, and shows that these variables are closely associated with the presence of ALN metastasis at diagnosis. Furthermore, Tseng et al (2014) and Grigoriadis et al (2018) have demonstrated that other histological features may be associated with the presence of ALN with metastasis at diagnosis (lymphocytic lobulitis, size and number or location of germinal centres, etc.). These variables could also be used to evaluate BC patient outcome.…”
Section: Clinical and Pathological Factors Associated To Aln Metastasismentioning
confidence: 99%